DEVELOPMENT OF GENIALLY BASED EDUTAINMENT GAMES AS MEDIA TO IMPROVE STUDENT’S LEARNING MOTIVATION - Yusti Azra Maulidiyah; Ani Nur Aeni; Prana Dwija Iswara (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
The low students’ learning motivation influences the suboptimal learning process. The learning activities tend to be monotonous and make the students have a lack of interest in learning. Making creative and innovative media is an effort that can be made to improve students’ learning motivation. The research aims to develop genially based edutainment game learning as media that can encourage and cultivate students' learning enthusiasm. The research used the Research & Development (R&D) method and the Borg & Gall development model. The research instruments used were validation questionnaires, trial sheets, and learning motivation questionnaires. The research results indicate that edutainment games based on Genially are valid and suitable for use as a learning media to help teachers in Civic Education learning activities. This is supported by the validation results from three experts of media, materials, and learning, with an average value of 88% in the highly valid category. The average score of learning motivation before applying media was 3.31 in the